2020
DOI: 10.37610/dyo.v0i70.567
|View full text |Cite
|
Sign up to set email alerts
|

Un análisis de revisiones de modelos y algoritmos para la optimización de planes de aprovisionamiento, producción y distribución de la cadena de suministro

Abstract: El propósito de este artículo es analizar los diferentes modelos y algoritmos utilizados para la optimización de planes de aprovisionamiento, producción y distribución en la cadena de suministro a través de las últimas revisiones de la literatura realizadas en este campo. Este estudio pretende proporcionar a los investigadores un punto de partida para la selección de modelos y algoritmos para la resolución de este tipo de problemas en la cadena de suministro y presentar varias líneas de investigación futuras.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…As analytical methods are not completely efficient in finding suitable solutions for such problems, a future research line in the topic under study is to propose heuristic and matheuristic approaches that deal with highly complex logistic plans that involve managing large amounts of data. Matheuristics could give logistic enterprises and confer global supply SCs shorter computation times when solving NP-hard and complex problems with different stakeholders distributed along the value chain [69].…”
Section: Cloud Computing (Cl)mentioning
confidence: 99%
“…As analytical methods are not completely efficient in finding suitable solutions for such problems, a future research line in the topic under study is to propose heuristic and matheuristic approaches that deal with highly complex logistic plans that involve managing large amounts of data. Matheuristics could give logistic enterprises and confer global supply SCs shorter computation times when solving NP-hard and complex problems with different stakeholders distributed along the value chain [69].…”
Section: Cloud Computing (Cl)mentioning
confidence: 99%
“…org/10.37610/dyo.v0i79.635 días por delante). Si bien son muy aplicadas en el mercado energético, por ejemplo, como metodologías que optimizan la compra de electricidad (Guzmán, M. P., Rubia, Peris & Alfalla-Luque 2021), o en planes de aprovisionamiento, producción y distribución de la cadena de suministros (Guzmán, E., Poler & Andrés 2020), también son aplicadas en el transporte tanto para el análisis de flujo de vehículos como de velocidad o tiempo (Ermagun and Levinson, 2018). Actualmente, la aplicación de técnicas de predicción en el transporte se basa en el aprendizaje automático y la teoría estadística (Poonia, Jain and Kumar, 2018).…”
Section: Dirección Y Organizaciónunclassified
“…In this research, 13 criteria are identified based on an exhaustive review of the literature (see [8,18,25,27,106,107]) and the assessments of experts in the field of operations research. These criteria are presented in Table 2.…”
Section: Stage 1-define Criteria and Alternativesmentioning
confidence: 99%
“…The replenishment (source), production (make) and distribution (deliver) planning problem type is determined by the SCOR (Supply Chain Operation Reference) methodology [106,108] (see Figure 3). Each problem type has its own characteristics and computational difficulty.…”
Section: C1 Problem Typementioning
confidence: 99%